Peran Pancasila Sebagai Sistem Etika Dalam Pencegahan Kecanduan Game Online Di Kalangan Remaja - Wianda Putri Hakiki; Saskia Meirisa; Shelvia Marsyah; Assyifa Dwi Yanti; Nailatul Khaira; Wilda Nafisyah Qonita; Revaldo; Febry Dedi Syaputra; Hikmal Permana; Elwidarifa Marwenny (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
This study is a literature review that aims to understand the role of Pancasila as an ethical system in preventing online game addiction among adolescents. The issues addressed in this study focus on how the values embedded in Pancasila can shape adolescents' character to help them exercise self-control and use technology wisely. The research questions explored include: (1) how Pancasila functions as an ethical system in everyday practice, and (2) how this role can help anticipate online game addiction among teenagers. Pancasila not only serves as the foundation of the state but also contains moral values that can guide individuals to act wisely amid digital developments. This study employs a descriptive qualitative approach by reviewing five relevant academic journals to gain a deeper understanding of the relationship between Pancasila ethics and adolescents’ digital behavior. The findings indicate that Pancasila values can be implemented through character education in schools, active parental involvement in shaping children's personalities, and a supportive social environment that fosters discipline and self-awareness. Consistent application of these values can help adolescents avoid addictive gaming behavior and develop a sense of responsibility in digital life. Thus, Pancasila plays a strategic role as an ethical system capable of instilling noble values in facing the challenges of the digital era.